2008
DOI: 10.1021/cm703369s
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Structure of a Cesium Aluminosilicate Geopolymer: A Pair Distribution Function Study

Abstract: The atomic pair distribution function (PDF) method was used to study the structure of cesium aluminosilicate geopolymer (CsThe geopolymer was prepared by reacting metakaolin with cesium silicate solution followed by curing at 50 °C for 24 h in a sealed container. Heating of Cs-geopolymer above 1000 °C resulted in formation of crystalline pollucite (CsAlSi 2 O 6 ). PDF refinement of the pollucite phase formed displayed an excellent fit over the 10-30 Å range when compared with a cubic pollucite model. A poorer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 44 publications
3
99
0
Order By: Relevance
“…The disordered nature of the geopolymer binder phase is highly amenable to analysis by this technique, as has been discussed in recent reviews [1,17], and significant advances in the understanding of geopolymer nanostructure have been obtained by both X-ray [18,19] and neutron [20,21] pair distribution function analysis. In situ analysis of geopolymer formation has previously been undertaken by a variety of laboratory and beamline techniques, including in particular the use of in situ energy-dispersive X-ray diffractometry to provide direct kinetic information regarding gel structure formation using high-energy synchrotron radiation [22,23].…”
Section: In Situ Neutron Pair Distribution Function Analysis Of Geopomentioning
confidence: 99%
“…The disordered nature of the geopolymer binder phase is highly amenable to analysis by this technique, as has been discussed in recent reviews [1,17], and significant advances in the understanding of geopolymer nanostructure have been obtained by both X-ray [18,19] and neutron [20,21] pair distribution function analysis. In situ analysis of geopolymer formation has previously been undertaken by a variety of laboratory and beamline techniques, including in particular the use of in situ energy-dispersive X-ray diffractometry to provide direct kinetic information regarding gel structure formation using high-energy synchrotron radiation [22,23].…”
Section: In Situ Neutron Pair Distribution Function Analysis Of Geopomentioning
confidence: 99%
“…[38][39][40] 3.2.2. X-ray absorption techniques for studying short-range order and chemical states Synchrotron-based XAS techniques provide element-selective complementary information about the local structure and chemical speciation of the selected element by fine-tuning the X-ray photon energy to the absorption edge of the absorber.…”
Section: Techniques For Characterizing Amorphous Phasesmentioning
confidence: 99%
“…The inability of this naming scheme to describe non-integer Si/Al ratios, and the inappropriateness of describing the three-dimensional structure of the alkali aluminosilicate gel according to this essentially chain-like terminology, mean that it is no longer used in a scientific context as the understanding of geopolymer materials has further advanced. However, the connections between zeolite chemistry and geopolymer gel structure which were proposed in this paper have since been advanced and now form the backbone of the modern chemical description of alkali aluminosilicate binder gels [29,30]. The mechanism of reaction was proposed to take place via 'still hypothetical monomers, the orthosialate ions' [28]; these ions have since been identified specifically as part of the array of small silicate and aluminosilicate species which are present in concentrated aqueous alkaline solutions [31,32], Figure 3.…”
Section: Points Raised By Davidovits (1991) [28]mentioning
confidence: 99%
“…Pair distribution function analysis is based on the use of high-resolution, high-energy X-ray or highmomentum transfer neutron scattering data to directly define and determine interatomic correlation distances [43], and therefore has obvious relevance to the study of construction materials based on calcium silicate or alkali aluminosilicate gels which are ordered only on a very short length scale [44,45]. This technique has been applied with significant success to the analysis of geopolymer materials [30,39,[44][45][46][47], and has in fact demonstrated that the fundamental binder phase is quite ordered on a length scale of up to approximately 8-10 Å, with the exact radius on which correlations are observed varying as a function of the binder chemistry (alkali cation and Si/Al ratio).…”
Section: Revisiting the 2007 'State Of The Art' [34]mentioning
confidence: 99%